Big Bergaya-Steam In Improving Scientific Reasoning Of Elementary School Students - Pertiwi, Senja; Setiawan, Bramianto (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The scientific reasoning ability of elementary school students still needs to be improved, particularly in understanding cause-and-effect relationships, making predictions, and drawing conclusions based on observational results. This problem was identified in science learning on the topic of forces in Grade IV of SDN Taman Rahayu 04, where most students tended to memorize concepts without being able to explain phenomena logically. This study aims to develop STEAM-based Big Bergaya media as a learning medium capable of helping students understand the concept of forces while training their scientific reasoning skills. The research employed a Research and Development (R&D) method using the 4D model, consisting of the define, design, develop, and disseminate stages. The research subjects comprised 21 Grade IV students of SDN Taman Rahayu 04. Data were collected through expert validation sheets, observations, teacher and student response questionnaires, and pretest and posttest assessments. The results showed that the developed media had a very high validity level with CVR and CVI values of 1.00. The media also achieved a practicality level of 91.19%, categorized as very practical. Furthermore, the effectiveness test results indicated an N-Gain value of 0.71 in the high category and Cohen's d effect size of 1.583. These findings indicate that STEAM-based Big Bergaya media is effective in improving students' scientific reasoning ability in elementary school science learning.